2009
DOI: 10.1142/s0217732309030576
|View full text |Cite
|
Sign up to set email alerts
|

Does Chiral Fermion Coupled to a Background Dilaton Field Preserve Information?

Abstract: A model where chiral boson is coupled to a background dilaton field is considered to study the s-wave scattering of fermion by a back ground dilaton black hole. It is found that the scattering process of chiral fermion does not violate unitarity and information remains preserved. Faddevian anomaly plays a crucial role on the information scenario.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…We have seen various examples with the crucial dependence of information loss with anomaly via the exploitation of ambiguity in the articles presented earlier in different times [6,7,10,20,21]. The present one has enlarged this list to confirm more convincingly the crucial role of anomaly towards the information preserving scenario with the support of the standard and powerful technique of imposition of chiral constraint [5].…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…We have seen various examples with the crucial dependence of information loss with anomaly via the exploitation of ambiguity in the articles presented earlier in different times [6,7,10,20,21]. The present one has enlarged this list to confirm more convincingly the crucial role of anomaly towards the information preserving scenario with the support of the standard and powerful technique of imposition of chiral constraint [5].…”
Section: Discussionsupporting
confidence: 63%
“…Although in the article [7], the s-wave scattering of chiral fermion off dilaton black-hole rendered a result with nonpreservation of information, in our article [10], we have shown that s-wave scattering of chiral fermion with generalized Faddeevian anomaly [11] leads to an information preserving result. This information preserving result related to information loss scenario of course is a gift of the Faddeevian anomaly and it indeed agrees with Hawking's revised suggestion [12].…”
Section: Pacs Numbersmentioning
confidence: 96%
See 3 more Smart Citations